PERTANGGUNGJAWABAN PIDANA TENAGA KESEHATAN DALAM KASUS MALPRAKTIK MEDIS: STUDI LITERATUR YURISPRUDENSI INDONESIA - Gunawan Widjaja (Jurnal Kesehatan, 2026)
This study examines the criminal liability of healthcare professionals in cases of medical malpractice, using a literature review of Indonesian case law. The focus of the study is on the concept of criminal liability, its legal basis, and the patterns of judicial reasoning in ruling on medical malpractice cases. The method employed is normative legal research through a review of primary, secondary and tertiary legal sources, including legislation, health law literature and relevant court rulings. The findings indicate that criminal liability for healthcare professionals can only be imposed if the following elements are proven: fault, a deviation from professional standards, a causal link, and a result that causes harm to the patient. Indonesian case law shows that judges tend to exercise caution in distinguishing between medical risk, medical negligence and malpractice; consequently, criminal penalties are only imposed where there is a serious breach for which legal liability can be established. This study emphasises the importance of striking a balance between patient protection and legal certainty for healthcare professionals in order to achieve a fair and accountable healthcare system.